Marketing with More: An In-depth Look at Relationship Marketing with New Media in the Green Industry - Scott Stebner; Lauri M. Baker; Hikaru Hanawa Peterson; Cheryl R. Boyer (Journal of Applied Communications, 2017)
Garden-center businesses have unique challenges related to the marketing of products. New and social media offer a way for garden-center operators to connect with customers and market products online in an effort to compete with box stores. The purpose of this qualitative case study was to explore how some garden-center businesses use social media and email marketing to build relationships with customers. Findings from eight in-depth interviews indicate garden-center stakeholders believe they are practicing relationship marketing through their e-newsletter and Facebook accounts. However, strategic planning is limited to an e-newsletter, marketing efforts show characteristics of one-way communication, and strategic measurement is absent. Lack of measurement could hinder the formation of profitable relationships. Owners, employees, and customers place high importance on educational content shared via social networks, but view advertising through new media differently. It is recommended garden-center owners and employees implement relationship-marketing techniques based on strategic measurement and planning to produce loyal brand advocates.
Keywords: Case study; Green Industry; New-media Marketing; Relationship Marketing; Social-Media Marketing